(untitled) (Euro-Asia Conferences, 2021)
The actuality of the theme of the present article is vivid in fact that many defectologists in all countries of the world study English, so teaching foreign language, particularly English can be easier and effective with the help of different innovations. Using innovations is based on improving the areas of vocabulary and grammar; different skills: reading, listening, speaking, and writing by using various innovations. It is important to make clear which one will be the main aim to focus on at a lesson.